18F-FDG PET/CT findings in patients with Kikuchi disease - Kong, E.; Chun, K.; Hong, Y.; Hah, J.; Cho, I. (Nuklearmedizin - NuclearMedicine, 2013)
Purpose: Kikuchi disease (KD) is a benign and self-limited syndrome characterized by cervical lymphadenopathy. This study evaluated 18F-fluorodeoxyglucose positron emission tomography/ computed tomography (FDG PET/ CT) findings in patients with KD and analyzed their imaging features. Patients, material, methods: We evaluated the FDG PET/CT findings of 22 patients (14 men, 8 women) with KD, ranging in age from 9 to 73 years. All patients had been diagnosed based on the pathological findings of biopsy. We examined the locations, metabolic activity and size of hypermetabolic lymph nodes (LNs) on FDG PET/CT imaging with medical history including laboratory results. Results: Among the 22 patients, we identified 619 hypermetabolic LNs which had maximum standard uptake value (SUVmax) above 3.0. The 16 patients were studied with FDG PET/CT to identify the cause of fever, another 5 patients for their neck masses, and the remaining patient for his left inguinal mass. Hypermetabolic LNs were noted in neck (18 bilaterally, 2 right, 1 left) of 21 patients, axilla of 10, mediastinum of 9, abdomen of 17, pelvis of 6, and inguinal area of 3. The SUVmax of FDG uptake in affected LNs by patient base analysis were 6.2–29.4. Of the 619 hypermetabolic LNs identified, 440 LNs (71.1%) were less than 10 mm in their short axis determined by CT, and were occasionally aggregated. No patient showed solid organ hypermetabolic lesion in FDG PET/CT. Conclusion: Kikuchi disease could present multiple hypermetabolic LNs in body on FDG PET/CT. Based on the physical findings, consideration of the generalized distribution of the relatively small-sized hypermetabolic LNs, FDG PET/CT may be useful as a diagnostic tool in cases of Kikuchi disease.
Keywords: Kikuchi disease; lymphadenopathy